Pembelajaran Menulis Cerpen dengan Menggunaakan Pendekatan Kontekstual (contextual teaching and learning) - susi hardianti; ika mustika; indra permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Short story writing learning is generally considered a difficult thing for students to do because of the equivalence of titles, themes and storylines that are difficult to balance by students so that when writing short stories many students have difficulty in expressing ideas to finish writing in written stories. This research was conducted at Padalarang Vocational High School, which is located in Padalarang, West Bandung Regency. This study aims to foster interest in writing, especially in writing short stories. The formulation of the problem faced in this research is How is the implementation of learning and the results of writing short text using a contextual approach ?. This research method uses descriptive qualitative and uses data collection techniques in the form of skills tests. Based on the results of research during learning activities indicate that the activities of short story writing using an approach (contextual teaching and learning) are very good with an average result of 18.32 with a percentage of 91.60% where the prensetase is included as very good criteria.                                                                                                           Keywords: Learning, Short Story Writing, Contextual